Predicting soil organic matter stability in agricultural fields through carbon and nitrogen stable isotopes. (September 2015) - De Clercq, Tim; Heiling, Maria; Dercon, Gerd; Resch, Christian; Aigner, Martina; Mayer, Leo; Mao, Yanling; Elsen, Annemie; Steier, Peter; Leifeld, Jens; Merckx, Roel
Abstract: In order to evaluate the sustainability and efficiency of soil carbon sequestration measures and the impact of different management and environmental factors, information on soil organic matter (SOM) stability and mean residence time (MRT) is required. However, this information on SOM stability and MRT is expensive to determine via radiocarbon dating, precluding a wide spread use of stability measurements in soil science. In this paper, we test an alternative method, first developed by Conen et al. (2008) for undisturbed Alpine grassland systems, using C and N stable isotope ratios in more frequently disturbed agricultural soils. Since only information on carbon and nitrogen concentrations and their stable isotope ratios is required, it is possible to estimate the SOM stability at greatly reduced costs compared to radiocarbon dating. Using four different experimental sites located in various climates and soil types, this research proved the effectiveness of using the C/N ratio and δ 15 N signature to determine the stability of mOM (mineral associated organic matter) relative to POM (particulate organic matter) in an intensively managed agro-ecological setting. Combining this approach with δ 13 C measurements allowed discriminating between different management (grassland vs cropland) and land use (till vs no till) systems. With increasing depth the stability of mOM relative to POM increases, but less so under tillage compared to no-till practises. Applying this approach to investigate SOM stability in different soil aggregate fractions, it corroborates the aggregate hierarchy theory as proposed by Six et al. (2004) and Segoli et al. (2013). The organic matter in the occluded micro-aggregate and silt & clay fractions is less degraded than the SOM in the free micro-aggregate and silt & clay fractions. The stable isotope approach can be particularly useful for soils with a history of burning and thus containing old charcoal particles, preventing the use of 14 C to determine the SOM stability. Highlights: C:N ratio and δ 15 N signature of soil fractions are used as proxy for SOM stability. The approach was tested on four agricultural site in Austria and Belgium. Adding δ 13 C signatures to model made it possible to distinguish between different management and land use systems. Applying this approach to soil aggregate fractions, it corroborates the aggregate hierarchy theory. Also useful approach for soils containing old charcoal particles, preventing use of 14 C to determine the SOM stability.